Identification of novel antigens contributing to autoimmunity in cardiovascular diseases - Müller, Anna-Maria; Bockstahler, Mariella; Hristov, Georgi; Weiß, Christel; Fischer, Andrea; Korkmaz-İçöz, Sevil; Giannitsis, Evangelos; Poller, Wolfgang; Katus, Hugo; Kaya, Ziya (Clinical immunology, 2016)
In myocarditis and dilated cardiomyopathy (DCM) patients the immune system may play an important role in disease progression. In this study, we aimed to identify new antigens as a target for autoimmune response that might play a crucial role in these diseases. Therefore, a peptide-array was used to investigate antibody binding profiles in patients with autoimmune myocarditis or DCM compared to healthy controls and thus to identify disease relevant antigens. To analyze the pathogenicity of the identified antigens, an experimental autoimmune myocarditis (EAM) model was used. Hereby, 3 peptide sequences, derived from myosin-binding-protein-C (MYBPC) fast-type, RNA-binding-protein 20 (RBM20), and dystrophin, showed pathogenic effects on the myocardium of mice. In summary, 3 potentially cardiopathogenic peptides (MYBPC fast-type, RBM20, dystrophin) were identified. Thus, this study could serve as a basis for future investigations aimed at determining further antigens leading to pathogenic effects on the myocardium of DCM as well as myocarditis patients.